Colistin Resistance Genes in Broiler Chickens in Tunisia - Antonietta Di Francesco; Daniela Salvatore; Sonia Sakhria; Fabrizio Bertelloni; Elena Catelli; Salma Ben Yahia; Aida Tlatli (Animals, 2023)
Colistin is a polymyxin antibiotic that has been used in veterinary medicine for decades, as a treatment for enterobacterial digestive infections as well as a prophylactic treatment and growth promoter in livestock animals, leading to the emergence and spread of colistin-resistant Gram-negative bacteria and to a great public health concern, considering that colistin is one of the last-resort antibiotics against multidrug-resistant deadly infections in clinical practice. Previous studies performed on livestock animals in Tunisia using culture-dependent methods highlighted the presence of colistin-resistant Gram-negative bacteria. In the present survey, DNA extracted from cloacal swabs from 195 broiler chickens from six farms in Tunisia was tested via molecular methods for the ten mobilized colistin resistance (mcr) genes known so far. Of the 195 animals tested, 81 (41.5%) were mcr-1 positive. All the farms tested were positive, with a prevalence ranging from 13% to 93%. These results confirm the spread of colistin resistance in livestock animals in Tunisia and suggest that the investigation of antibiotic resistance genes by culture-independent methods could be a useful means of conducting epidemiological studies on the spread of antimicrobial resistance.